2005
DOI: 10.1074/jbc.m508652200
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Mutant α1-Antitrypsin Z in the Endoplasmic Reticulum Activates Caspases-4 and -12, NFκB, and BAP31 but Not the Unfolded Protein Response

Abstract: In ␣ 1 -antitrypsin (␣1AT) deficiency, a polymerogenic mutant form of the secretory glycoprotein ␣1AT, ␣1ATZ, is retained in the endoplasmic reticulum (ER) of liver cells. It is not yet known how this results in liver injury in a subgroup of deficient individuals and how the remainder of deficient individuals escapes liver disease. One possible explanation is that the "susceptible" subgroup is unable to mount the appropriate protective cellular responses. Here we examined the effect of mutant ␣1ATZ on several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
239
5
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(263 citation statements)
references
References 42 publications
17
239
5
2
Order By: Relevance
“…Several previous studies have shown that the intracellular accumulation of the a1AT mutant Z protein is associated with caspase activation and other markers of apoptosis in in vitro systems. 4,5,8,9 Furthermore, when in vivo model systems are examined, an increased rate of hepatocellular proliferation is present, suggesting a compensatory response to increased hepatocellular death. 3 However, when either a homozygous ZZ human liver or a model transgenic mouse liver has been examined, widespread evidence of hepatocellular death has not been readily apparent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several previous studies have shown that the intracellular accumulation of the a1AT mutant Z protein is associated with caspase activation and other markers of apoptosis in in vitro systems. 4,5,8,9 Furthermore, when in vivo model systems are examined, an increased rate of hepatocellular proliferation is present, suggesting a compensatory response to increased hepatocellular death. 3 However, when either a homozygous ZZ human liver or a model transgenic mouse liver has been examined, widespread evidence of hepatocellular death has not been readily apparent.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Our laboratory and others have reported a series of studies that have begun to examine the mechanism of liver cell injury in a1AT deficiency. [3][4][5][6][7][8][9] The data suggest that an …”
mentioning
confidence: 88%
See 2 more Smart Citations
“…However, several reports have convincingly demonstrated that the UPR is not activated either in numerous cultured cell lines (15,45,46) or in transgenic mice (47). The exact mechanism(s) by which the protein-accumulated protein leads to cellular injury is still unknown, but is currently under intense investigation.…”
Section: Mechanisms Of Cellular Injurymentioning
confidence: 99%